COMSOL-based investigation of the characteristics of microscopic water flooding and residual oil distribution in carbonate reservoirs - Jia, Pin; Guo, Hongxin; Wang, Yichen; Peng, Cong; Cheng, Linsong; Ke, Xianzhe (Frontiers in Earth Science, 2022)
Carbonate reservoirs are rich in oil and gas reserves and have great exploitation potential. It is of great significance to carry out the research on the microscopic mechanism of carbonate reservoirs. In this paper, based on the thin section images of core casting of typical Wells in actual reservoirs, three kinds of images representing the pore and throat structure of real rocks were designed by image stitching and binarization processing methods, and the microscopic pore model of carbonate rocks was established by COMSOL numerical simulation software. The microscopic water flooding characteristics and residual oil distribution of different schemes were observed by designing different fracture development forms. It is found that fractures developed in parallel main lines have more obvious influence on water flooding characteristics than fractures developed in vertical main lines. The cluster residual oil is the main residual oil type in the early stage of water flooding in the pure matrix model. With the progress of water flooding, the continuous cluster residual oil gradually turns into discontinuous porous residual oil and columnar residual oil, and the porous residual oil and columnar residual oil become the main types. Vertical mainline fractures reduce the amount of residual oil in clusters and replace it with columnar residual oil. Parallel main line fractures expand the unswept area, and the residual oil is all contiguous clusters. This paper analyzes the law and characteristics of water flooding in carbonate reservoir from microscopic Angle, and provides key theoretical support for enhancing oil recovery.